Avaliação física e funcional do idoso - Gobbi, Sebastião [UNESP]; Gobbi, Lilian T.B. [UNESP]; Ferreira, Leandro [UNESP]; Sebastião, Emerson [UNESP] (My University, 2007)
When aiming to prescribe and supervise physical activity for the elderly, the stages of diagnosis and control of programming are of relevant importance and the evaluation of functional capacity should be included both in the above mentioned stages and in the context of a multidimensional evaluation of basic attention to older people's health. The instruments used to assess the functional capacity comprise the questionnaire-like scales (e.g. Katz and Lawton & Brody - designed to assess dependency/independency to cope with basic and instrumental activities of daily living, respectively) and/or specific motor tests for the elderly (e.g. AAHPERD or Fullerton or CS-PFP batteries of tests) and/or laboratorial tests of exertion (e.g. VO2max and blood lactate concentration). The selection of assessment techniques should be based on the following criteria: a) validity (whether they measure what they are supposed to measure - face, criterion and discriminant validity); b) reliability (whether they are reproducible in terms of inter and intra rater agreement); c) normative (present a set of scores against which we can compare and classify the results of the tests related to the overall population, with the same features); d) feasible in terms of administration (time devoted to the application, financial costs, assessment of a large number of participants) and; e) health-functional fitness gradient of the older person.
Physical and functional evaluation in the elderly
Keywords: Aging; Evaluation; Functional capacity; Physical activity